WDR36 Safeguards Self-Renewal and Pluripotency of Human Extended Pluripotent Stem Cells - An, Shiyu; Yao, Dan; Zhang, Wenyi; Sun, Hao; Yu, Tianyi; Jia, Ruizhe; Yang, Yang (Frontiers in Genetics, 2022)
Extended pluripotent stem cells (EPS cells) have unlimited self-renewal ability and potential to differentiate into mesodermal, ectodermal and endodermal cells. Notably, in addition to developing the into embryonic (Em) lineages, it can also make an effective contribution to extraembryonic (ExEm) lineages both in vitro and in vivo. However, multiple mysteries still remain about the underlying molecular mechanism of EPS cells' maintenance and developmental potential. WDR36 (WD Repeat Domain 36), a protein of 105 kDa with 14 WD40 repeats, which may fold into two β-propellers, participates in 18sRNA synthesis and P53 stress response. Though WDR36 safeguards mouse early embryonic development, that is homozygous knockout of WDR36 can result in embryonic lethality, what role does WDR36 plays in self-renewal and differentiation developmental potential of human EPS cells is still a subject of concern. Here, our findings suggested that the expression of WDR36 was down-regulated during human hEPS cells lost self-renewal. Via constructing inducible knockdown or overexpressing WDR36-human EPS cell lines, we found that WDR36 knockdown disrupted self-renewal but promoted the mesodermal differentiation of human EPS cells, however, overexpressing of WDR36 had little effect. Additionally, P53 inhibition could reverse the effects of WDR36 knockdown, on both self-renewal maintenance and differentiation potential of human EPS cells. These data implied that WDR36 safeguards self-renewal and pluripotency of human EPS cells, which would extend our understanding of the molecular mechanisms of human EPS cells’ self-renewal and differentiation.